249 Effectiveness of a dose-based concept for dust control – a longitudinal study of coal miners' in the ruhr area. (24th April 2018) - Yong, M; Anderle, L; Derwall, R; Lenaerts, H; Morfeld, P
Abstract : Introduction: A dose-based concept for dust control has been implemented in German coal mining since 1991. This concept foresees that miners with exposure to fibrogenic dusts cannot exceed a cumulative exposure of 440 total dust exposure value (TDEV) per year within an assessment period of 2 years. TDEV is defined to be a function of the 8 hour shift average concentration and the number of performed shifts. The Regulation of Health Protection in Mining set the work place limit at an 8 hour average of 4.0 mg/m3 for respirable dust and 0.2 mg/m3 for quartz component (>5% mass). This concept considers the exposure limits, and regulatory changes connecting to working durations, hence, cumulative personal exposure to dust. The present study evaluates the effectiveness of this concept, after 37 years of implementation. Methods: A complete inception cohort of 1369 coal miners who started working underground in the Ruhr area in 1974–1979 has been provided with continuous health surveillance. Concerning the course of lung function (VCmax, FEV1, FEV1/VCmax), the impacts of exposure metrics are estimated using Generalised Estimation Equation models. The risk of developing coal workers' pneumoconiosis (CWP) category ≥0/1 is estimated by Cox regression. Results: Cumulative coal dust exposure shows no negative impact on VCmax and FEV1, but a very low but statistically significant effect on FEV1/VCmax. Cumulative exposure to coal dust shows a significant slightly increased risk of developing CWP ≥0/1. In an alternative model considering average dust concentration and exposure duration, increased risk is attributed to exposure duration, but not to dust concentration. Discussion: The dust control programme connecting regulation of working duration incorporate with continuous health surveillance seems to be effective for preventing CWP in German coal mining after 37 years of follow-up.